2022
DOI: 10.21203/rs.3.rs-1381728/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Family function, Work Engagement, and Sleep on the Mental Health of Nurses in China's Top Three Hospitals : A Cross-sectional Study

Abstract: Objective This paper aims to explore the influence of family function, work engagement, and sleep on the mental health of nurses in China's top three hospitals. Method The convenience sampling method was adopted to select 1147 clinical nurses from Taihe Hospital Affiliated to Hubei University of Medicine, during the period of August-September 2018 as the survey subjects. APGAR, UWES-9, PSQI,SCL-90 were employed to conduct a questionnaire survey on nurses’ family function, work engagement, sleep quality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Chen et al studied the health care benefit of sound in forest therapy. By analyzing human psychology and emotional state in forest sound, they believed that birdsong, water sounds, and sounds of wind blowing leaves could exert a high positive impact on human psychology [26]. Song et al selected two environments, urban and forest, and confirmed that forest sound therapy had a moderating effect on the negative emotions of tired working ladies, and forest sound could alleviate fatigue symptoms, but the effect of short-term forest recuperation was limited [27].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al studied the health care benefit of sound in forest therapy. By analyzing human psychology and emotional state in forest sound, they believed that birdsong, water sounds, and sounds of wind blowing leaves could exert a high positive impact on human psychology [26]. Song et al selected two environments, urban and forest, and confirmed that forest sound therapy had a moderating effect on the negative emotions of tired working ladies, and forest sound could alleviate fatigue symptoms, but the effect of short-term forest recuperation was limited [27].…”
Section: Introductionmentioning
confidence: 99%